Proprioception analysis of patients with anterior cruciate ligament reconstruction - Erkurt, Nazım; Yerli, Mustafa; Yüce, Ali; Bayraktar, Tahsin Olgun; Atar, Sevgi; Turan, Kaya; Çabuk, Haluk (The European Research Journal, 2023)
Objectives: This study evaluates the effect of tibial stump mechanoreceptor preservation on proprioception, muscle strength, recovery and functional outcomes after arthroscopic anterior cruciate ligament surgery (ACLS). Methods: Patients undergoing ACLS between January-July 2019 were evaluated by a single surgeon. The HUMAC NORM 2 device measured patients’ proprioceptive sensation and muscle strength before and after surgery; KOOS and Oxford scales were used to score patients’ functional results. The patients were divided into two groups: those who underwent stump-preserving surgery (SP group) and those who underwent conventional surgery (C group). Results: Our study evaluated 27 patients, 11 in the SP and 16 in the C groups. The two groups had no statistical difference in muscle strength, proprioception, and functional scores in the first and third postoperative months. In the sixth-month evaluation, significantly better functional scores were found in the C group. Further, the athletic function was better in patients with good proprioception recovery, regardless of the group comparison. Conclusions: Preserving the stump and mechanoreceptors on the tibial face was not determined to provide additional benefit to the patients in the first six months after surgery. Returning to sports was faster and functional scores were better in patients with good proprioception recovery.